Effectiveness of HOTS-Based Multiple Representation Learning Model in Circular Motion Material - Intan Kusumawati; Sumarli Sumarli; Sutopo Sutopo; Sentot Kusairi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2020)
Students’ Higher Order Thinking Skills (HOTS) can be honed by gradually developing new concepts from their multiple representation abilities through HOTS-based multiple representation learning models. This study aims to determine the effectiveness of the implementation of HOTS -based multiple representation learning models on circular motion material. The method used is in the form of quantitative research — the study design used pre-experimental design. The sampling technique is purposive sampling of physics education students. It was found that HOTS-based multiple representation learning models on circular motion material effectiveness were achieved as expected in this study, the effectiveness of 1.06. The statistical hypothesis test used in the form of U Mann Whitney with the results of Asymp. Sig. 0.04 < 0.05, the hypothesis is accepted, meaning that there is the influence of the application of HOTS based multiple representation learning model on student learning outcomes in circular motion material. Improved learning outcomes were shown from the results of the average pretest score of 50.0 and the post-test of 85.9 with N-Gain of 0.7 in the high category. The positive response of students to the application of this learning model shows a percentage value of 96.7% with very strong.